2005
DOI: 10.1007/s10620-005-2561-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Labeling by Monoclonal Antibodies Adnab-9 and Anti-?-Defensin 5 Based on the Distribution and Adenomatous Tissue Content of Colonic Polyps

Abstract: We sought a correlation between site and morphology of colonic polyps by labeling with neoplastic and general Paneth cell markers, monoclonal antibodies Adnab-9 and anti-alpha-defensin 5, respectively. Proportions labeled by Adnab-9 and anti-alpha-defensin 5 were, respectively, 42 and 85% for adenomas, 39 and 63% for early tubular adenomas, 41 and 44% for serrated, 34 and 20% for mixed, and 11 versus 2.7% for hyperplastic polyps. Compared with hyperplastic polyps, the proportion of other polyps labeled by Adna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Ullah et al [27] were the first to examine HD-5 expression in colorectal polyps. They reported that 85% of CAs, 44% of serrated adenomas, 20% of MPs, and 2.7% of HPs showed HD-5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ullah et al [27] were the first to examine HD-5 expression in colorectal polyps. They reported that 85% of CAs, 44% of serrated adenomas, 20% of MPs, and 2.7% of HPs showed HD-5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Adnab-9 monoclonal antibody (mouse ascites) was used at a 1:1,000 dilution and the substrate was 3-amino-9-ethyl-carbazole (AEC). AD5 (kindly supplied by Dr. T. Ganz, UCLA) was used at 1:5,000 as described previously [17], to label hyperplastic and PJS polyp sections. Due to limitations of the tissue supply, FJP sections were not labeled for a-defensin 5.…”
Section: Immunohistochemistrymentioning
confidence: 99%